Massive Squamous Cell Carcinoma of the Orbit: A Rare Case Report - Smriti Nagpal Gupta; Sushil Kumar; Ruchi Goel; Charu Sagar; Okram Birbala (Journal of Clinical and Diagnostic Research, 2017)
Squamous Cell Carcinoma (SCC) is the second most common eyelid malignancy worldwide. SCC is an aggressive tumour, with the ability to cause significant morbidity, mortality and the risk of rapid spread. Hence, urgent diagnosis and management is essential. SCC may mimic other benign and malignant lesions. Its definite diagnosis is generally done by biopsy and immunohistochemistry. Orbital invasion warrants treatment by orbital exenteration. There are chances of incomplete tumour clearance and recurrence, with a five year survival Rate of about 60%. Herein, we describe a young male patient with a massive tumour engulfing the entire orbit, and spilling over to the surface and periocular skin. There was a fungating, multilobulated mass of about 10 X 10 cm in size, with areas of necrosis and secondary infection. The tumour had invaded and destroyed all the orbital structures. However, the nasal cavity and maxillary sinus was free of tumour and there was no evidence of metastasis. The patient underwent surgical debulking of the tumour via orbital exenteration, followed by adjuvant radiotherapy. Histopathology revealed, well differentiated SCC. On follow up, the patient was systemically well, with no evidence of metastasis and the surgical site appeared healthy.